Brockton Public Library interior, drawing room bay windows detail, Brockton, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Interior detail of the drawing room bay windows. Built in 1913. Library is located at 304 Main Street, Brockton, Massachusetts. (Source: Brockton Public Library website).; Caption on image: Library (7) Int, det, drawing rm bay windows 309 Main St.; Binder Number 4. Pocket Number: 6.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.